2004
DOI: 10.1023/b:joih.0000045253.19409.02
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and HIV Risk Among a Sample of Mexican and Puerto Rican Women

Abstract: The disproportionate impact of HIV/AIDS on Hispanic women in the United States has been variously attributed to a failure to utilize protective measures due to low levels of HIV knowledge, a denial or minimization of risk, and conflicts with cultural norms. It has been hypothesized that women's relative lack of power in relationships may be associated with higher risk sexual behavior. We examined the relationship between higher risk sexual behavior and perceived locus of control in sexual relationships among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…People with an external locus of control believe that they cannot influence outcomes through their own efforts-they perceive extrinsic risk. Studies in Western cultures show that external LOC was associated with teen pregnancy (Young et al 2001(Young et al , 2004, "risky" sexual behavior (Loue et al 2004), externalizing behaviors (Jackson et al 2000), and positive attitudes toward promiscuous sexuality (Werner-Wilson 1998)-traits indicative of mating effort strategies.…”
Section: Psychological Mechanisms For Human Life History Variationmentioning
confidence: 99%
“…People with an external locus of control believe that they cannot influence outcomes through their own efforts-they perceive extrinsic risk. Studies in Western cultures show that external LOC was associated with teen pregnancy (Young et al 2001(Young et al , 2004, "risky" sexual behavior (Loue et al 2004), externalizing behaviors (Jackson et al 2000), and positive attitudes toward promiscuous sexuality (Werner-Wilson 1998)-traits indicative of mating effort strategies.…”
Section: Psychological Mechanisms For Human Life History Variationmentioning
confidence: 99%
“…Earlier studies have emphasized the salience of cultural nuances and unique contextual challenges to HIV/STI-related behaviors, such as immigration, acculturation, and citizenship status (Afable-Munsuz, & Brindis, 2006;Espinoza, Hall, Selik, & Hu, 2008;Lopez-Quintero, Shtarkshall, & Neumark, 2005;Loue et al, 2004;Zambrana, Cornelius, Boykin & Lopez, 2004). Comparisons of Latino subgroups living in the United States also demonstrated lower levels of HIV-related education and knowledge, rates of HIV testing, and perceived risk of HIV among Mexicans and Mexican Americans (Lopez-Quintero et al, 2005;Loue, Copper & Fieldler, 2003;Loue, Cooper, Traore, & Fiedler, 2004;Zambrana et al, 2004).…”
mentioning
confidence: 99%
“…Comparisons of Latino subgroups living in the United States also demonstrated lower levels of HIV-related education and knowledge, rates of HIV testing, and perceived risk of HIV among Mexicans and Mexican Americans (Lopez-Quintero et al, 2005;Loue, Copper & Fieldler, 2003;Loue, Cooper, Traore, & Fiedler, 2004;Zambrana et al, 2004). In the United States, women of Mexican origin constitute the largest Latina subgroup (54.3%), yet a dearth of culturally specific research and interventions exist (American College of Physicians, 2000;Harvey et al, 2004;Herbst et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of that study shed further light on the idea that low relationship power and the incorporation of gender roles that diminish women are factors that contribute to women developing beliefs that they have little control over their own motivations, thoughts, emotional states and behavioral patterns regarding safe sex (Bowleg, Belgrave & Reisen, 2000). Another study conducted with 150 Hispanic women with high rates of risky sexual behavior reported the existence of a belief that the locus of control over what happens in their sex life belongs to the man (Loue, Cooper, Traore & Fiedler, 2004). This means that these women believe that everything concerning their own sexual life depends on and must be decided by their partners.…”
Section: Gender Roles and Power Imbalancementioning
confidence: 99%